A systematic review of prescribing criteria to evaluate appropriateness of medications in frail older people. Issue 4 (November 2014) - Poudel, A; Peel, NM; Mitchell, C; Nissen, LM; Hubbard, RE
Summary This study systematically reviews the published literature regarding inappropriate prescribing in frail individuals aged at least 65 years. Twenty-five of 466 identified studies met the inclusion criteria. All papers measured some surrogate indicators of frailty, such as performance-based tests, cognitive function and functional dependency. Beers criteria were used in 20 studies (74%) to evaluate inappropriate medication use and 36% (9/25) studies used more than one criterion. The prevalence of inappropriate medications ranged widely from 11 to 92%. Only a few studies reported the relationship between potentially inappropriate medication use and surrogate measures of frailty. These diverse findings indicate the need for a standardized measure for assessing appropriateness of medication in frail older individuals. Prescribing tools should address both medication and patient-related factors such as life expectancy and functional status to minimize inappropriate prescribing in frail individuals.